2013
DOI: 10.1128/jcm.03314-12
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Bacterial Colonization Associated with Urothelial Cells from Patients with Chronic Lower Urinary Tract Symptoms

Abstract: c Chronic lower urinary tract symptoms (LUTS), such as urgency and incontinence, are common, especially among the elderly, but their etiology is often obscure. Recent studies of acute urinary tract infections implicated invasion by Escherichia coli into the cytoplasm of urothelial cells, with persistence of long-term bacterial reservoirs, but the role of infection in chronic LUTS is unknown. We conducted a large prospective study with eligible patients with LUTS and controls over a 3-year period, comparing rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
237
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(249 citation statements)
references
References 36 publications
9
237
0
3
Order By: Relevance
“…In particular, most in vivo relevant lipopeptides are triacylated and, therefore, are adequately modeled by Pam3Cys used in our study (28,64). Respiratory viruses that can activate TLR2 (29,63) also have been associated with MS exacerbations (31,32,61). In addition, EBV, which is strongly associated with MS susceptibility (30), is able to activate the transcription factor NF-kB and the production of the chemokine CCL2 in a TLR2-dependent manner (65,66).…”
Section: Foxp3mentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, most in vivo relevant lipopeptides are triacylated and, therefore, are adequately modeled by Pam3Cys used in our study (28,64). Respiratory viruses that can activate TLR2 (29,63) also have been associated with MS exacerbations (31,32,61). In addition, EBV, which is strongly associated with MS susceptibility (30), is able to activate the transcription factor NF-kB and the production of the chemokine CCL2 in a TLR2-dependent manner (65,66).…”
Section: Foxp3mentioning
confidence: 98%
“…Our present findings provide a possible link between urinary and respiratory infections and T cell dysregulation that may lead to MS clinical exacerbations (relapses) (31,32,61,62), because the cell walls or outer membranes of Gram-negative bacteria, such as Escherichia coli, as well as Staphylococcus saprophyticus and other Gram-positive bacteria, which are typically involved (61,62), contain TLR2 agonists (29,63). In particular, most in vivo relevant lipopeptides are triacylated and, therefore, are adequately modeled by Pam3Cys used in our study (28,64).…”
Section: Foxp3mentioning
confidence: 99%
“…We chose this species because it is the most invasive bacteria seen in our patient group [6]. Briefly, fresh liquid cultures of bacteria were challenged with a dilution series of the drug capsules, compared with a similar series of control capsules and with injectiongrade unencapsulated gentamicin solution used in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Shielded from the host immune system and from antibiotics in the bladder lumen, such bacterial reservoirs can persist and later emerge to initiate a fresh round of acute infection [4]. Recent studies have shown that UTI is also associated with other species of chronic, invasive bacteria besides E. coli, including Enterococcus faecalis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggested that women with recurrent UTI should endure evaluation and treatment of episodes of infection to prevent the development of oversensitive detrusor. Other studies showed that positive urine culture at 10 5 CFU/ml in women is significantly associated with lower urinary tract symptoms, such as nocturia, urgency, urgency incontinence, and nocturnal enuresis [21,22]. Additionally, bacteriuria is also associated with bladder pain.…”
Section: Chronic Inflammation and Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 96%